2019
DOI: 10.1002/aqc.3094
|View full text |Cite
|
Sign up to set email alerts
|

Encouraging youth engagement in marine protected areas: A survey of best practices in Canada

Abstract: A holistic approach to stakeholder participation is emerging where youth are increasingly being recognized as core stakeholders in community‐based conservation efforts. A growing number of youth‐focused marine conservation initiatives and representation at international marine conservation conventions demonstrate that youth are taking an active role in marine conservation worldwide. This paper surveys current best practices in youth engagement in marine protected areas (MPAs) in Canada, across 10 different eng… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 22 publications
(42 reference statements)
0
3
0
Order By: Relevance
“…Although the intention to address this deficiency was enshrined in the Brundtland report -Our Common Future (Brundtland 1987) -the impacts have yet to match the intentions. However, the trend to include diverse stakeholders has been positive, bringing youth engagement as a core approach to achieve present and future conservation goals (Chen et al 2019;Pardo et al 2020). In this article, we highlight the findings and recommendations of a report -Review: youth engagement and intergenerational partnership across IUCN (Zurba et al 2021) -commissioned by the IUCN and applicable to other conservation organizations.…”
Section: Pathway To Mainstream Youth Engagement and Intergenerational...mentioning
confidence: 97%
See 1 more Smart Citation
“…Although the intention to address this deficiency was enshrined in the Brundtland report -Our Common Future (Brundtland 1987) -the impacts have yet to match the intentions. However, the trend to include diverse stakeholders has been positive, bringing youth engagement as a core approach to achieve present and future conservation goals (Chen et al 2019;Pardo et al 2020). In this article, we highlight the findings and recommendations of a report -Review: youth engagement and intergenerational partnership across IUCN (Zurba et al 2021) -commissioned by the IUCN and applicable to other conservation organizations.…”
Section: Pathway To Mainstream Youth Engagement and Intergenerational...mentioning
confidence: 97%
“…However, the trend to include diverse stakeholders has been positive, bringing youth engagement as a core approach to achieve present and future conservation goals (Chen et al . 2019; Pardo et al . 2020).…”
Section: Figurementioning
confidence: 99%
“…Popularize ocean-related knowledge for youth, raise citizens' awareness of marine ecological protection, promote public participation. Including citizens in the construction of MPAs so that they can become part of the construction of MPAs (Chen et al, 2019;Zhang, 2020); 2) Considering the balance of local economic and ecological environment development (Zeng et al, 2016), that can avoid over-exploitation of the marine ecological environment by vigorously developing an aquatic product processing industry and guiding fishermen to switch to processing; and 3) Reasonably carry out implementation of marine engineering, strengthen research on the impact of large water-related projects on protected areas (Gao et al, 2007). Discussing and proposing corresponding protection countermeasures, and manage the feasibility demonstration, implementation, and post-project evaluation.…”
Section: Classifications and Management Recommendationsmentioning
confidence: 99%
“…However, special attention must be paid to the design of CCS programs to provide opportunities for students to be involved in and position themselves as actors in the many steps of the scientific process [40]. Previous research has explored this to understand better what might enable or constrain student participation [41][42][43][44]. Together, these authors found three factors to be important: (1) contextual factors, like facilitators and available roles [41]; (2) setting norms and cultures (i.e., how are participants positioned) [42]; and (3) clear communication of program goals and objectives [43].…”
Section: Engage Students In Community and Citizen Science As A Partic...mentioning
confidence: 99%
“…Previous research has explored this to understand better what might enable or constrain student participation [41][42][43][44]. Together, these authors found three factors to be important: (1) contextual factors, like facilitators and available roles [41]; (2) setting norms and cultures (i.e., how are participants positioned) [42]; and (3) clear communication of program goals and objectives [43]. Well-designed programs have been found to impact students' development of science identity, self-efficacy, and interest [42,45], as well as learning and agency [5].…”
Section: Engage Students In Community and Citizen Science As A Partic...mentioning
confidence: 99%